Tableting properties of microcrystalline cellulose obtained from wheat straw measured with a single punch bench top tablet press - Jovana Krivokapić; Jasna Ivanović; Jelena Djuriš; Djordje Medarević; Zorica Potpara; Zoran Maksimović; Svetlana Ibrić (Saudi Pharmaceutical Journal, 2020)
The objective of this work was to study the relation between the manufacturing conditions of microcrystalline cellulose (MCC), its physicochemical properties and its tableting behavior. Two different preparation procedures were used to produce MCC from wheat straw, utilizing an acid hydrolysis method, either using only sulfuric acid or combination of sulfuric and hydrochloric acid. The tableting behavior of obtained MCC samples and mixtures of MCC with ibuprofen was studied using a dynamic powder compaction analyzer. It was observed that some of the obtained MCC samples showed better flowing properties than commercially available Vivapur® PH101 and also very high values of tensile strength, solid fraction and elastic recovery. This can be linked with its good compaction behavior, but on the other hand it can cause problems with the disintegration of the tablets. In mixtures with ibuprofen, MCC samples showed lower values of tensile strength, while on the other hand elastic recovery did not seem to be much affected, still exhibiting very high values. According to the obtained results, it can be concluded that MCC obtained from the agricultural waste could have satisfactory properties for tablet preparation by the direct compression method. Further studies are needed to optimize process conditions in order to achieve better physicochemical characteristics, especially in terms of elastic recovery.